2017
DOI: 10.1038/s41598-017-12515-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein-associated Phospholipase A2 Is Associated with Risk of Mild Cognitive Impairment in Chinese Patients with Type 2 Diabetes

Abstract: Type 2 diabetes mellitus (T2DM) is a low-grade chronic inflammatory diseases, which have been implicated in the pathogenesis of cognitive decline. We aim to evaluate associations between inflammatory markers and the risk of mild cognitive impairment (MCI) in T2DM. This study of 140 diabetic patients involved 71 with MCI and 69 controls. Clinical parameters, neuropsychological tests, high sensitivity C reactive protein (hsCRP), interleukin-6 (IL-6), lipoprotein-associated Phospholipase A2 (Lp-PLA2) mass and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…Our findings were similar to a cross-sectional study from Scotland [12], which has shown that IL-6 was associated with estimated lifetime cognitive status after adjusting for vocabulary, education level, cardiovascular dysfunction, duration of diabetes, and glycemic control in older patients with T2D. The findings of a recent study from China have also suggested that plasma hs-CRP was associated with the risk of MCI among T2D patients [11]. Meanwhile, another Chinese case-control study in T2D has reported that the patients with MCI have a significantly higher hs-CRP than those without MCI, but CRP was not significantly correlated with the cognitive status [34].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings were similar to a cross-sectional study from Scotland [12], which has shown that IL-6 was associated with estimated lifetime cognitive status after adjusting for vocabulary, education level, cardiovascular dysfunction, duration of diabetes, and glycemic control in older patients with T2D. The findings of a recent study from China have also suggested that plasma hs-CRP was associated with the risk of MCI among T2D patients [11]. Meanwhile, another Chinese case-control study in T2D has reported that the patients with MCI have a significantly higher hs-CRP than those without MCI, but CRP was not significantly correlated with the cognitive status [34].…”
Section: Discussionsupporting
confidence: 89%
“…In previous, one cohort study of 168 Chinese elderly patients has demonstrated that plasma high-sensitivity C-reactive protein (hs-CRP) level was associated with cognitive function and development of dementia in non-diabetics [10]. Currently, several epidemiological studies have focus on the association between inflammatory markers and the risk of MCI in T2D patients [11, 12], which showed that hs-CRP or IL-6 were found to be associated with the risk of MCI among T2D patients. Moreover, it has been reported that MCI was often associated with folate [8] and folic acid supplementation appeared to improve cognitive function and reduce blood levels of Aβ-related biomarkers in MCI [13].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by data showing that higher Lp-PLA2 mass/activity is an independent risk factor for MCI in type 2 diabetes mellitus patients. In light of these observations, Lp-PLA2 might represent a central player in the vicious circle leading to the accumulation of inflammatory cells and cytokines and vascular deficit [ 96 ].…”
Section: Lipoprotein Phospholipase A2 (Lp-pla2)mentioning
confidence: 99%
“…These clinical studies indicate Lp‐PLA2 as an independent risk factor for these inflammation‐related conditions. In addition, another study observed that Lp‐PLA2 is associated with a higher risk of developing mild cognitive impairment in type two diabetes mellitus patients . Thus, this inflammatory factor can be used as an indicator of multiple diseases depending on context.…”
Section: Introductionmentioning
confidence: 99%